EFFECT OF DIFFERENT CONCENTRATIONS OF INDOLBUTYRIC ACID IN THE ROOTING OF CUTTINGS OF Annona muricata “GUANÁBANA” IN SUBIRRIGATION CHAMBER - PÉREZ ORTIZ, Víctor Reyger (2019)
The objective of the investigation was to determine the effect of different concentrations of Indolbutyric Acid (AIB) on the rooting of Annona muricata «Guanabana» cuttings in the sub-irrigation chamber, which was developed in the agroforestry vivarium of the Universidad Nacional Intercultural de la Amazonía (UNIA), located at km 0.63 of the San José de Tushmo road, Yarinacocha district, Coronel Portillo province, Ucayali region, Perú, between the months of August to October of 2017. Soursop cuttings were collected, cutting the twigs with pruning shears, with 10-12 cm in length, and a diameter of 0.5 cm, and then cutting half of the leaves with a scalpel. The cuttings were disinfected with fungicide, for 10 minutes and ventilated for 10 minutes, then they were introduced about 1 cm from their base, in a container containing the different AIB solutions, by 3 seconds, and with the help of a fan were dried for 1 minute, so that the alcohol evaporates and the hormone can be fixed, and then installed inside the subirrigation chamber according to the treatments studied (0 ppm of AIB, 1000 ppm of AIB, 2000 ppm of AIB and 3000 ppm of AIB); concluding that, for the number of roots, the control treatment (0 ppm of AIB) and the treatment with 2000 ppm AIB, presented the best averages (3.55 and 3.39 roots respectively), not finding significant differences between treatments for the length of roots, and for the percentage of rooted cuttings, the treatment with 1000 ppm of AIB, presented the best average (41%) and finally, for the percentage of survival, the treatment with 2000 ppm of AIB presented the best average (99.33 %).